2022
DOI: 10.3390/pr10030584
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Activity of Fresh Noodles Formulated with Flour-Bran Blends Varied by Particle Size and Blend Ratio of Purple-Colored Wheat Bran

Abstract: This study explored the noodle-making performance of flour blends with different particle sizes and blending ratios of purple-colored wheat bran and their antioxidant properties. The bran particle size was reduced using an ultra-centrifugal mill equipped with 1, 0.5, and 0.2 mm sieves. The damaged starch and swelling capacity of the bran were analyzed. Quality of the flour-bran blends at different blending ratios was analyzed by solvent retention capacity (SRC). Noodles made from the blends and their correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Next, 1 ml of Na2CO3 solution was added, and the absorbance was measured using a wavelength of 765 nm. Antioxidant activity testing was performed using the DPPH method modified by Park et al [25]. The sample extract was added to 2 ml of DPPH methanol solution.…”
Section: ) Elasticity Of Noodlementioning
confidence: 99%
“…Next, 1 ml of Na2CO3 solution was added, and the absorbance was measured using a wavelength of 765 nm. Antioxidant activity testing was performed using the DPPH method modified by Park et al [25]. The sample extract was added to 2 ml of DPPH methanol solution.…”
Section: ) Elasticity Of Noodlementioning
confidence: 99%
“…The capability of flour containing purple-colored wheat bran to make noodles was improved by the decrease in the bran's particle size. This is due to an increase in the amount of bran used to make noodles with health advantages [135].…”
Section: Particle Size Reductionmentioning
confidence: 99%
“…The total phenol and flavonoid contents and antioxidant capacity of the noodles were lower compared to their original flours. Noodles prepared from a blend of regular and black or purple wheat flours have been found to possess higher amounts of total phenols and anthocyanins than that made from regular wheat flour alone [ 51 ]. These studies show that adding colored wheat milling fractions to pastas and noodles improve their content of anthocyanins, polyphenols, and antioxidant properties.…”
Section: Purple Wheat Productsmentioning
confidence: 99%
“…It has also been reported that purple wheat bran-enriched muffins exhibit reasonable levels of anthocyanins along with promising antioxidant properties, despite the significant reduction in total phenolic content and ORAC values during the processing of muffins [ 53 ]. Similarly, ABTS values have been found to increase significantly by replacing portions of common wheat flour with purple wheat bran in fresh noodles, e.g., 79 µmol TE/100 g for regular wheat noodles compared with 246, 315, and 487 µmol TE/100 g for noodles prepared with 10, 30, and 50% replacement levels of purple wheat bran [ 51 ]. A similar trend has been observed in the case of DPPH with a 3- to 4-fold increase in noodles containing purple wheat bran.…”
Section: Health-enhancing Properties Of Purple Wheat Foodsmentioning
confidence: 99%